Lixamento do Pinus elliotti com carbeto de silício e óxido de aluminio - Leite, Sueli Souza [UNESP] (2013)
The Sanding is a complex process involving many variables that affect the quality of the part produced, working mainly in the timber industry in the production of panels (MDF, MDP, HDF, etc...) and furniture. However, these industries use the sanding process empirically, not optimizing it. The aim of this study was to compare the behavior of sandpaper white aluminum oxide (OA-white) and Black silicon carbide (SiC-black), analyzing variables in the process as: strength, power, emission, vibration, wear particle size of sanding, and its consequences on the surface finish of the workpiece. Made the process of plane grinding samples of Pinus elliottii, processed in parallel to the fibers, which were sanded with sandpaper grain OA white and black 3-SiC abrasive conditions (new, moderately eroded and severely eroded) grain sizes in 3 (80, 100, and 120 mesh). 6 replicates was performed for each condition tested. Each trial was captured output variables of the sanding process: strength, power, emission and vibration. With two stages totaling 108 trials. After the sanded samples, it has the same surface quality by raising the surface roughness Ra. Through experiment, it can be concluded that abrasives OA-white tended to have higher strength, power, emissions and less vibration in the sanding process, compared to the SiC-black. However, surface finish exhibited similar to the particle size of 80 to 100 mesh, worn abrasive conditions. However, the particle size of 120 mesh, obtained by the roughness of sandpaper OA-bank was higher compared to SiC-black to all conditions of sandpaper due to its toughness